บทบาทของระบบข้อมูลเพื่อการตัดสินใจและเครื่องชี้วัดการพัฒนาจังหวัด: The Roles of Provincial Development Information System and Performance Indicators - แสนทวีสุข กิตติพัฒน์ (Journal of Applied Economics and Management Strategy, 2018)
การวางแผนและการพัฒนาเศรษฐกิจในระดับจังหวัด มีการดำเนินงานโดยส่วนราชการในจังหวัด ซึ่งมีการวางแผนพัฒนาตามระบบราชการ ตามกรอบงบประมาณ และยุทธศาสตร์จังหวัดซึ่งสอดคล้องกับนโบายการพัฒนาระดับประเทศ โดยผลของการเปลี่ยนแปลงทางเศรษฐกิจในจังหวัด สามารถประเมินและติดตามผลการดำเนินงานผ่านเครื่องชี้วัดการพัฒนาจังหวัดและระบบข้อมูลเพื่อการตัดสินใจ เพื่อให้ผู้เกี่ยวข้องสามารถติดตามผลลัพธ์ที่สะท้อนความเป็นอยู่ของประชาชน โดยมีข้อมูลผลผลิตซึ่งเกิดจากแต่ละโครงการพัฒนาในจังหวัดประกอบเพื่อให้เห็นการเปลี่ยนแปลง มีการจัดเก็บแยกไปตามหน่วยงานราชการในจังหวัดที่มีระบบจัดเก็บที่แตกต่างกันไป ทำให้ระบบข้อมูลในระดับจังหวัดยังคงไม่ได้พัฒนาอย่างเต็มศักยภาพในการจัดเก็บเพื่อการพัฒนา จึงควรมีการออกแบบระบบข้อมูลที่มีหน่วยในการวิเคราะห์ระดับครัวเรือนและคำนึงถึงแนวทางการใช้ Big Data ซึ่งจะช่วยลดปัญหาการไม่ใช้ข้อมูลในการวางแผนและพัฒนาในระดับจังหวัด Provincial economic development and planning is conducted by the provincial administrative office. Using the government budget, development plans are conducted concordantly with provincial strategic plan and central government policies. The outcomes of the development should be evaluated and monitored through employing key performance indicators and database system for decision-making. Consequently, stakeholders would be able to acquire information concerning the livelihood of the citizen. The development project output data is collected in various formats by each provincial administrative office. This causes the lack of using information system and performance indicators in each province. The database should be collected on household level basis and parallel with Big Data designed to eliminate the less usage of data in provincial development plan.